1 The ATI score (age-thrombotic burden-index of microcirculatory resistance) in stemi: a cardiac magnetic resonance study. (27th November 2017) - Maria, GL De; Alkhalil, M; Wolfrum, M; Dawkins, S; Langrish, J; Lucking, A; Choudhury, R; Channon, K; Kharbanda, R; Banning, A
Abstract : Background: The age-thrombus score-index of microcirculatory resistance (ATI) score is a diagnostic tool recently applied by our group in ST elevation myocardial infarction (STEMI). It is able to predict suboptimal myocardial reperfusion early in the revascularisation process thus facilitating the triage of alternative or additional therapies to the conventional approach with stenting. We aimed to validate the ATI score against cardiac magnetic resonance imaging (cMRI). Methods: The ATI score was calculated using age (>50=1 point), pre-stenting index of microcirculatory resistance (IMR) (>40 and <100=1 point; ≥100=2 points) and angiographic thrombus score (4=1 point; 5=3 points)]. cMRI scan was performed within 48 hours from admission and at 6 months follow up to assess the extent of infarct size (IS%) and microvascular obstruction (MVO%). Results: The ATI score was calculated prospectively in 80 STEMI patients. cMRI scanning was performed within 48 hours in all patients and in 50 patients at six months follow up. ATI score was closely related to final IS% (ATI0-1: 18.0% [9.0–24.5], ATI2-3: 28.5% [12.8–43.0] and ATI4-5-6: 41.2% [22.0–44.4] p: 0.001) and with MVO% (ATI0-1: 0.0% [0.0–0.9], ATI2-3: 0.7% [0.0–2.5] and ATI4-5-6: 4.1% [1.2–10.7], p<0.001). ATI score predicted final IS% at six months follow up (ATI0-1: 12.7% [4.5–22.0], ATI2-3-: 20.0% [6.4–25.6] and ATI4-5-6: 34.0% [22.2–46.5], p: 0.02). Conclusions: The ATI score applied prior to stenting in patents with STEMI, can predict the likelihood of MVO% and IS% both acutely and at six months follow up cMRI.